Over Dimension Over Loading in Indonesia: A Systemic Analysis of Policy Impasses and Pathways to a Sustainable Multimodal Future - Abdullah Ade Suryobuwono; Lis Lesmini; Edi Abdurachman; Sita Aniisah Sholihah (Siber Nusantara Research, 2025)
The phenomenon of Over Dimension Over Loading (ODOL) in Indonesia has evolved into a systemic issue impacting transportation infrastructure, logistics, and public safety. ODOL practices, involving the operation of vehicles with loads or dimensions exceeding legally defined limits, have become widely accepted despite the presence of clear legal frameworks. This research aims to analyze the root causes of the ODOL problem and develop an integrated multimodal policy model to reduce ODOL violations in Indonesia. Using Soft Systems Methodology (SSM), the research proposes a policy approach that includes enhancing governance, implementing surveillance technologies such as Weigh-in-Motion (WIM), calibrating progressive penalties, and shifting modal transport to rail and sea. These recommendations are designed to address non-compliance with regulations and create a more efficient and sustainable transportation system.